The end of aspiration? : social mobility and our children's fading prospects - Exley, Duncan (Policy Press, 2019)
Duncan Exley draws on expert research and real life experiences - including from an actor, a politician, a billionaire entrepreneur and a surgeon - to issue a wake-up call to break through segregated opportunity. He offers a manifesto to reboot our prospects and benefit all.